Epidemiology of bacterial conjunctivitis in chinchillas (Chinchilla lanigera): 49 cases (2005 to 2015). (April 2017) - Ozawa, S.; Mans, C.; Szabo, Z.; Di Girolamo, N.
Abstract : Objectives: To evaluate the anamnesis, clinical signs, diagnostic test results, treatment and outcome of chinchillas diagnosed with bacterial conjunctivitis. Methods: Medical records of 49 chinchillas diagnosed with bacterial conjunctivitis were retrospectively reviewed. Association between clinical signs and type of bacteria involved was determined by means of univariate logistic regression. Results: 61·5% of the isolated bacteria were Gram‐negative, and the most common bacterial species was Pseudomonas aeruginosa (50%), followed by Staphylococcus species (26·9%). Chinchillas with acute conjunctivitis (1 to 3 days) were much more commonly affected by Gram‐negative organisms. The majority of chinchillas that presented with concurrent respiratory signs were diagnosed with P. aeruginosa . Clinical resolution of conjunctivitis was reported in 87·8% chinchillas with a median time to clinical resolution of 17·5 days. Susceptibility of P. aeruginosa isolates to potentiated sulphonamides, enrofloxacin, ciprofloxacin, gentamicin, amikacin and polymyxin B was 8·3, 36, 62·5, 88·5, 100 and 100%, respectively. Clinical Significance: P. aeruginosa is the predominant bacterial species associated with bacterial conjunctivitis in chinchillas. With the exception of duration of clinical signs, information on the anamnesis or physical examination findings cannot aid in distinguishing conjunctivitis caused by P. aeruginosa or other Gram‐negative bacteria from the ones caused by Gram‐positive bacteria. Gentamicin‐ or polymyxin B‐containing antibiotic formulations are recommended for empirical topical therapy.